Pengukuran Beban Kerja Mental dan Tingkat Kelelahan pada Pegawai Daily Check (DC) PT Kereta Api Indonesia (Persero) Depo Lokomotif Tanjungkarang Menggunakan Metode Draws dan Metode Sofi - Delvya Icha Sriningru (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
Employee performance is the quality and quantity of work results achieved by an employee in carrying out it in accordance with the responsibilities given. Efforts to improve employee performance include paying attention to the level of workload experienced by employees. Is there a relationship between the mental workload between age and the length of time working for Daily Check employees and is there a relationship between the level of fatigue between age and the length of time working for Daily Check employees? What management efforts can be made to reduce the mental workload and fatigue levels of DC employees? This research aims to determine the mental workload and fatigue levels of daily inspection employees using the DRAWS Method and SOFI Method. The research also wanted to find out whether there was a relationship between mental workload, age and length of service for daily check employees. The results obtained by the research show that the mental workload of daily check employees is included in the overload category. The level of physical fatigue of employees is at a moderate level. There is a strong negative relationship between work mental load and age and length of service. Recommendations for reducing the mental workload of daily check employees are to provide training, time management, stress management skills, recognition, appreciation and regular evaluation.